Gold(III) π‐Allyl Complexes. Issue 4 (5th December 2019) - Rodriguez, Jessica; Szalóki, György; Sosa Carrizo, E. Daiann; Saffon‐Merceron, Nathalie; Miqueu, Karinne; Bourissou, Didier
Abstract: Gold(III) π‐complexes have been authenticated recently with alkenes, alkynes, and arenes. The key importance of Pd II π‐allyl complexes in organometallic chemistry (Tsuji–Trost reaction) prompted us to explore gold(III) π‐allyl complexes, which have remained elusive so far. The (P, C)Au III (allyl) and (methallyl) complexes 3 and 3′ were readily prepared and isolated as thermally and air‐stable solids. Spectroscopic and crystallographic analyses combined with detailed DFT calculations support tight quasi‐symmetric η 3 ‐coordination of the allyl moiety. The π‐allyl gold(III) complexes are activated towards nucleophilic additions, as substantiated with β‐diketo enolates. Abstract : Go for gold : The π coordination of allyl moieties to (P, C) coordinated gold(III) has been authenticated and shown to promote nucleophilic addition. Spectroscopic and crystallographic analyses combined with detailed DFT calculations support tight quasi‐symmetric η 3 ‐coordination of the allyl moiety.